Attitudes of nursing faculty members toward technology and e-learning in Lebanon - Rona Nsouli; Dimitrios Vlachopoulos (BMC, 2021)
Abstract Background Our transition to an "information society" means that Information and Communication Technology (ICT) has become integral to our lives. ICT has also become an essential aspect of medical institutions and healthcare settings. Healthcare professionals, especially nurses are required to use ICT in their daily work. In Lebanon, however, due to political factors, many universities have not introduced technology or any form of ICT in their curricula. Institutions of higher education do use technology in various ways, however, successful incorporation of ICT in education requires acceptance by instructors who are expected to use ICT in teaching practices. Although international findings reveal that ICT should be used in nursing education, some faculty members experience difficulty integrating it. Method A mixed methodological research approach was used to investigate the attitudes of nursing teaching staff toward the use of ICT in nursing education. Results Our findings revealed three categories of faculty with differing attitudes to the use of ICT in teaching and learning: pioneers, faculty members who have developed positive attitudes toward ICT usage; followers, faculty members with neutral attitudes; and resisters, faculty members with negative attitudes. Conclusions Identification of the nursing faculty members' attitude toward ICT and the challenges faced by them contributes to the integration of ICT into nursing curricula and further development of educational practices.